Transcriptional responses indicate acclimation to prolonged deoxygenation in the coral Stylophora pistillata - Kvitt, Hagit; Malik, Assaf; Ben-Tabou de-Leon, Smadar; Shemesh, Eli; Lalzar, Maya; Gruber, David F.; Rosenfeld, Hanna; Shi, Tuo; Mass, Tali; Tchernov, Dan (Frontiers in Marine Science, 2022)
The current decrease in oceanic dissolved oxygen is a widespread and pressing problem that raises concern as to how marine biota in general, and coral reefs in particular will be affected. However, the molecular response underlying tolerance of corals to prolonged severe deoxygenation where acclimation to hypoxia can accrue is not yet known. Here, we investigated the effect of two weeks of continuous exposure to conditions of extreme deoxygenation, not hitherto exerted under laboratory conditions ( 0.35 mg L−1 dissolved oxygen), on the physiology and the diurnal gene expression of the coral, Stylophora pistillata. Deoxygenation had no physiologically significant effect on tissue loss, calcification rates, symbiont numbers, symbiont chlorophyll-a content and symbiont photosynthesis rate. However, deoxygenation evoked a significant transcriptional response that was much stronger at night, showing an acute early response followed by acclimation after two weeks. Acclimation included increased mitochondria DNA copy numbers, possibly increasing energy production. Gene expression indicated that the uptake of symbiosis-derived components was increased together with a decrease in nematocyst formation, suggesting that prolonged deoxygenation could enhance the corals’ need for symbiosis-derived components and reduces its predation abilities. Coral orthologs of the conserved hypoxia pathway, including oxygen sensors, hypoxia-inducible factor (HIF) and its target genes were differentially expressed in a similar temporal sequence as observed in other metazoans including other species of corals. Overall, our studies show that by utilizing highly conserved and coral–specific response mechanisms, S. pistillata can acclimate to deoxygenation and possibly survive under climate change-driven oceanic deoxygenation. On the other hand, the critical importance of algal symbionts in this acclimation suggests that any environmental perturbations that disrupt such symbiosis might negatively affect the ability of corals to withstand ocean oxygen depletion.